Recent Advances and Future Research Directions for Hearing Loss Treatment Based on Nanoparticles. (17th January 2022) - Dindelegan, Maximilian George; Blebea, Cristina; Perde-Schrepler, Maria; Buzoianu, Anca Dana; Maniu, Alma Aurelia
Abstract : Sensorineural hearing loss is a prevailing health issue worldwide which usually occurs due to sensory inner ear cell destruction. These cells, once damaged, do not regenerate in mammals resulting in permanent hearing loss. Effective treatment of inner ear diseases is strongly correlated with efficient drug delivery to the inner ear. Researchers have made important efforts to deliver drugs locally to the inner ear in a safe and controllable manner. Different strategies and drug delivery systems were used to mitigate the resistance exerted by the multiple anatomical barriers found in the inner ear. Nanoparticles represent an option for sustained drug delivery to the inner ear. Nanocarrier-based systems can diffuse through the round and oval window membrane allowing for direct delivery into the inner ear components. Certain types of enhanced nanoparticles can focus on specific parts of the inner ear, providing targeted delivery which might represent the future therapy for sensorineural hearing loss. In this article, we will present the latest advances in the treatment of hearing loss based on nanoparticles.